Antioxidant activity of chitooligosaccharides upon two biological systems: Erythrocytes and bacteriophages - Fernandes, João C.; Eaton, Peter; Nascimento, Henrique; Gião, Maria S.; Ramos, Óscar S.; Belo, Luís; Santos-Silva, Alice; Pintado, Manuela E.; Malcata, F. Xavier (Carbohydrate polymers, 2010)
Most of the reports to date on the antioxidant capacity of chitosans and chitooligosaccharides (COS) are based on strictly chemical methods. When studying antioxidants with potential in vivo applications, the method used to evaluate the antioxidant activity should be representative of the conditions in which the antioxidant might have a protective effect. In this work we evaluate the antioxidant activity of two COS mixtures and a low MW chitosan (LMWC) upon two biological oxidizable substrates – erythrocytes and phages, subjected to accelerated oxidation conditions. Our results suggest that COS/LMWC can be used as antioxidants in biological systems. All the tested compounds reduced either the hemolytic and DNA damage, by inhibiting H 2O 2- and AAPH-radicals. However, the results obtained for these biological assays did not reveal a dose dependence, contrary to the chemical assay, suggesting that the protective concentrations should be established, in order to prevent enhancement of the oxidative damage – i.e. a prooxidant effect.